Absoluta Generalidad y Validez lógica - Barrio, Eduardo Alejandro (2013)
The aim of this paper is to investigate various limiting results about the concept of validity. In particular, I argue that assuming the absolute generality thesis, the higher-order logic with standard semantics and plural logic cannot be sufficiently expressive to capture its own concept of validity. Moreover, I show that several modifications of classical logic leads to the same results limiting.